1986
DOI: 10.1159/000183911
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Calcifications in Children on Dialysis

Abstract: Pulmonary calcifications are known to occur in patients with chronic renal failure. Recently, scintigrams with bone-seeking radionuclides have been used to detect subclinical pulmonary calcium deposits. We studied 18 children on maintenance dialysis without evidence of pulmonary calcification on chest X-ray. Four children (22.2%) had a positive technetium 99m hydroxymethylene diphosphate scan (group 1), and 14 children had a negative scan (group 2). Mean serum aluminum levels were 2.68 ± 0.30 μmol/l (mean ± SD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

1989
1989
2010
2010

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…The authors suggested that the beneficial effect of Mg on carotid intima-media thickness might be due to the decreased serum PTH level. Furthermore, Mg-containing phosphate binders have been shown to be effective agents for controlling serum phosphorus and hyperparathyroidism in ESRD patients [76,77] .…”
Section: The Effect Of Mg On Athero-and Arteriosclerosis: Vascular Camentioning
confidence: 99%
“…The authors suggested that the beneficial effect of Mg on carotid intima-media thickness might be due to the decreased serum PTH level. Furthermore, Mg-containing phosphate binders have been shown to be effective agents for controlling serum phosphorus and hyperparathyroidism in ESRD patients [76,77] .…”
Section: The Effect Of Mg On Athero-and Arteriosclerosis: Vascular Camentioning
confidence: 99%
“…These calcifications may be of clinical relevance, as demonstrated in some of the patients with extensive pulmonary calcifications which showed abnormalities in single breath carbon monoxide diffusion capacity (DCO) (Conger et al 1975;Faubert et al 1980). This was not the case, however, in the children studied by Drachman et al (1986). Conger et al (1975) also found significant hypoxia and decreased vital capacity in his patients, but this was not confirmed in two other studies (Faubert et al 1980;Drachman et al 1986).…”
Section: Pulmonary Calcificationsmentioning
confidence: 68%
“…This was not the case, however, in the children studied by Drachman et al (1986). Conger et al (1975) also found significant hypoxia and decreased vital capacity in his patients, but this was not confirmed in two other studies (Faubert et al 1980;Drachman et al 1986). …”
Section: Pulmonary Calcificationsmentioning
confidence: 68%
See 2 more Smart Citations